2022
DOI: 10.1108/ecam-12-2021-1137
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on construction labor productivity: the case of Turkey

Abstract: PurposeThe aim of this study is to measure the impact of the factors affecting construction labor productivity by focusing on different types of construction works during and after the COVID-19 pandemic in Turkey, as well as discuss solutions and immediate actions.Design/methodology/approachThis research was conducted in two steps. First, a quantitative survey was carried out to determine the dimension of factors negatively affecting construction labor productivity and the loss rate of different construction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…from all over the world. A random sampling method was adopted in choosing respondents [26] to ensure an equal possibility of being selected for both parts of the survey. A total of 70 international respondents from 38 different countries took part in the survey.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…from all over the world. A random sampling method was adopted in choosing respondents [26] to ensure an equal possibility of being selected for both parts of the survey. A total of 70 international respondents from 38 different countries took part in the survey.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…A critical analysis of the 54 PPGCI articles reviewed in this paper revealed that four distinct PP themes were investigated, and these are presented in Figure 3. that Covid-19 had a significant negative impact on project performance in the construction industry, with the main impacts being reduced worker productivity (Al-Mhdawi et al, 2023;Oni et al, 2023;Wijayaningtyas et al, 2022), scarcity and cost increases of building materials due to supply chain disruptions (Alhammadi, 2022;Farooq et al, 2022;Gumusburun Ayalp & Çivici, 2022) and poor cash flows due to scarcity of construction projects during the pandemic (Oladimeji, 2022;Sami Ur Rehman et al, 2022;Tekin, 2022).…”
Section: Themes Investigated By Ppgci Articles During the Covid-19 Er...mentioning
confidence: 99%
“…Research by Rahman et al (2022) and Namous and Al Battah (2021) on what causes construction delays in developing nations found that a lack of skilled labor, ineffective management, and sloppy site management were all factors in the UAE. According to Tekin (2022), poor planning, insufficient contractors, and frequent changes to the project process and orders are to blame for the construction industry's delays in Turkey. When comparing actual and expected project results in the Gaza Strip, many different metrics are employed.…”
Section: Background Of the Studymentioning
confidence: 99%